The costs of information processing in an information ratchet system - Cheong, Jian Wei (2019)
The Landauer's Principle states that the erasure of a bit of information must dissipates \( k_B \ln2 \) amount of entropy. This spawned the field of information thermodynamics, studying how information are processed, and how it relates to the entropy of a thermodynamic system. However, Landauer's Principle fail to account for the structural costs associated with the implementation of the information processing devices, resulting in inefficient information processing. By studying the information ratchet system, which mediates interactions between a heat, work and information reservoirs, the relationship between information changes and energy flows can be quantified. A program is written to simulate the information ratchet system, allowing us to identify the need for a device to synchronise to its environment as a condition for efficient information processing. The existence of an unsurpassable bound that limits efficiency is also found. By studying the transient and modularity dissipations of information processing, it is clear that these device structural costs comes from the dissipation of unaccounted correlations between the device and the information reservoir, and the attempt to minimise these leads to the need for a device to synchronise to its environment.